Synthesis of β-prolinols via [3+2] cycloaddition and one-pot programmed reduction: Valuable building blocks for polyheterocycles. Issue 51 (21st December 2016) - Li, Jundong; Lin, Na; Yu, Lei; Zhang, Yandong
Graphical abstract: Highlights: Our chemistry provides an efficient approach to highly functionalized β -prolinols. The method features a [3+2] cycloaddition and a programmed reduction. The resulting β -prolinols are valuable building blocks for polyheterocycles. Abstract: A novel two-step synthesis of multisubstituted β -prolinols has been developed, featuring a [3+2] cycloaddition of azomethine ylides and a programmed reduction triggered by the combination of borane and lithium aluminum hydride (LAH). β -Prolinols are shown to be valuable building blocks for polyheterocycles.